The Zakat Maal Management In The National Zakat Agency, Palembang City - Rijalus Sholihin (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Purpose: The purpose of this study was to determine the management of Zakat Maal in the National Amil Zakat Agency (BAZNAS) of Palembang City and to determine the management of Zakat Maal l distribution in the National Amil Zakat Agency (BAZNAS) of Palembang City, and to find out the factors that are supporting and inhibiting the management of Zakat Maal in National Amil Zakat Agency (BAZNAS) in Palembang City. Design/Method/Approach: This type of research uses field research. Qualitative descriptive approach. Sources of data in this study are primary data and secondary data. Data collection techniques are observation, interview, and documentation. Data analysis techniques used in this study by descriptive methods such as data collection and then classified into data.